Large-eddy simulation and modelling of Taylor–Couette flow. (10th May 2020) - Cheng, W.; Pullin, D. I.; Samtaney, R.
Abstract : Abstract : Wall-resolved large-eddy simulations (LES) of the incompressible Navier–Stokes equations together with empirical modelling for turbulent Taylor–Couette (TC) flow are presented. LES were performed with the inner cylinder rotating at angular velocity [STIX]x1D6FA_i and the outer cylinder stationary. With R_i, R_o the inner and outer radii respectively, the radius ratio is [STIX]x1D702=0.909 . The subgrid-scale stresses are represented using the stretched-vortex subgrid-scale model while the flow is resolved close to the wall. LES is implemented in the range Re_i=10^5-10^6 where Re_i=[STIX]x1D6FA_iR_id/[STIX]x1D708 and d=R_o-R_i is the cylinder gap. It is shown that the LES can capture the salient features of the flow, including the quantitative behaviour of spanwise Taylor rolls, the log variation in the inner-cylinder mean-velocity profile and the angular momentum redistribution due to the presence of Taylor rolls. A simple empirical model is developed for the turbulent, TC flow for both a stationary outer cylinder and also for co-rotating cylinders. This consists of near-wall, log-like turbulent wall layers separated by an annulus of constant angular momentum. Model results include the Nusselt number Nu (torque required to maintain the flow) and measures of the wall-layer thickness as functions of both the Taylor number Ta and [STIX]x1D702 . These are compared with results from measurement, direct numerical simulation and the LES. A model extension to rough-wall turbulent flow is described. This shows an asymptotic, fully rough-wall state where the torque is independent of Re_i/Ta, and where NuTa^1/2 .